Satisfacción con la atención recibida en un servicio diferenciado para adolescentes de un establecimiento de salud de primer nivel de atención - Obregón-Morales, Danna Maribel (2021)
Objective: To determine adolescent satisfaction from the differentiated health care service at a primary health care institution in Lima. Materials and methods: An observational, descriptive and cross-sectional study conducted in 84 adolescents treated at the Centro de Salud El Progreso (Carabayllo). Satisfaction from health care was evaluated using the SERVQUAL questionnaire, which was adapted and validated, and showed reliability in its expectation and perception components. Results: Satisfaction from health care occurred in 28.57 % of the adolescents, most of whom were between 12 and 14 years old (83.33 %). Regarding the dimensions, empathy and security had the highest percentage of satisfaction (39.28 % and 36.90 %, respectively). The indicators physical appearance of the facilities (6.45 ± 0.82) and trust in health care (6.38 ± 0.84) presented the highest score in expectations. Conclusions: A small proportion of adolescents who attended the differentiated service were satisfied with the care received, while the empathy dimension was the one with the greatest number of adolescents who showed satisfaction.